1989, the year that never ended: epistemology and methodology of the research in Political Communication in Brazil - Marques, Francisco Paulo Jamil (2018)
This paper examines a relevant part of the Brazilian scientific production in Political Communication in order to assess the epistemological and methodological advances and flaws that have featured this area of expertise. The argument is divided into four parts. In the first one, we discuss different theoretical questions, ranging from the imprecision in the definition of objects and categories of research to a persistent conceptual outdatedness. Next, the text focuses on some of the most common methodological options found in empirical studies present in the field, diagnosing the predominance of a descriptive emphasis. The third section reflects on the consequences of the burdens previously pointed out: for example, research findings that tend to overestimate media effects. We conclude our argument by addressing some suggestions that may help to solve part of the problems here outlined.